Lead halide–templated crystallization of methylamine-free perovskite for efficient photovoltaic modules - Bu, Tongle; Li, Jing; Li, Hengyi; Tian, Congcong; Su, Jie; Tong, Guoqing; Ono, Luis K.; Wang, Chao; Lin, Zhipeng; Chai, Nianyao; Zhang, Xiao-Li; Chang, Jingjing; et al. (Science (American Association for the Advancement of Science), 2021)
Although formamidinium-based lead iodide (PbI 2 ) perovskites have a favorable bandgap and good thermal stability, the difficulty in controlling nucleation makes it difficult to grow high-quality, large-area films compared with methylammonium counterparts. Bu et al. show that adding N -methyl-2-pyrrolidone to the perovskite precursors forms an adduct with PbI 2 that promotes the formation of the desired black α-phase at room temperature. The addition of potassium hexafluorophosphate eliminated hysteresis by passivating interfacial defects and promoted long-term thermal stability at 85°C in unencapsulated devices. Large-area modules (17 square centimeters) achieved power conversion efficiencies of 20.4%. Science , abh1035, this issue p. 1327 Added N -methylpyrrolidone inhibits nucleation and enables growth of large-area α-phase formamidinium-based perovskite films. Upscaling efficient and stable perovskite layers is one of the most challenging issues in the commercialization of perovskite solar cells. Here, a lead halide–templated crystallization strategy is developed for printing formamidinium (FA)–cesium (Cs) lead triiodide perovskite films. High-quality large-area films are achieved through controlled nucleation and growth of a lead halide• N -methyl-2-pyrrolidone adduct that can react in situ with embedded FAI/CsI to directly form α-phase perovskite, sidestepping the phase transformation from δ-phase. A nonencapsulated device with 23% efficiency and excellent long-term thermal stability (at 85°C) in ambient air (~80% efficiency retention after 500 hours) is achieved with further addition of potassium hexafluorophosphate. The slot die–printed minimodules achieve champion efficiencies of 20.42% (certified efficiency 19.3%) and 19.54% with an active area of 17.1 and 65.0 square centimeters, respectively.